(untitled) (The Review of Diabetic Studies, 2025)
Acute Coronary Syndromes (ACS), including ST-elevation myocardial infarction (STEMI) and non-ST elevation myocardial infarction (NSTEMI), remain leading causes of global morbidity and mortality. Timely intervention during the pre-hospital phase is crucial for limiting myocardial damage and improving survival outcomes. This comprehensive review examines the impact of pre-hospital paramedic interventions on survival rates in ACS, with particular focus on early electrocardiogram (ECG) acquisition, pre-hospital thrombolysis, medication administration, and activation of percutaneous coronary intervention (PCI) pathways. Evidence demonstrates that paramedic-led care significantly reduces door-to-balloon time, enhances early reperfusion, and decreases mortality by enabling rapid initiation of treatment even before hospital arrival. Studies also reveal that integration of telemedicine, artificial intelligence, and enhanced clinical decision protocols further increase accuracy and speed of ACS diagnosis. However, variations in training, system resources, and geographical disparities influence the effectiveness of these interventions. This review highlights the critical contribution of paramedics as the first point of advanced medical contact, emphasizes their expanding role in modern cardiovascular care systems, and identifies strategies for optimizing pre-hospital management of ACS. Ultimately, findings confirm that early paramedic intervention is a key determinant in improving survival and reducing long-term complications among heart attack patients.